2007
DOI: 10.1002/pmic.200600746
|View full text |Cite
|
Sign up to set email alerts
|

Translational and transcriptional analysis of Sulfolobus solfataricus P2 to provide insights into alcohol and ketone utilisation

Abstract: The potential of Sulfolobus solfataricus P2 for alcohol or ketone bioconversion was explored in this study. S. solfataricus was grown in different concentrations (0.1-0.8% w/v) of alcohols or ketones (ethanol, iso-propanol, n-propanol, acetone, phenol and hexanol) in the presence of 0.4% w/v glucose. Consequently, the addition of these alcohols or ketones into the growth media had an inhibitory effect on biomass production, whereby lag times increased and specific growth rates decreased when compared to a gluc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

7
37
1

Year Published

2007
2007
2013
2013

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 20 publications
(45 citation statements)
references
References 53 publications
(39 reference statements)
7
37
1
Order By: Relevance
“…In S. solfataricus, besides Sso2536, 12 additional open reading frames (ORFs) encoding putative ADHs have been identified and annotated (adh-1 to -13). All but adh-9 are actively expressed, as demonstrated by proteome analyses (17,18). The presence of multiple ADH ORFs indicates a metabolic relevance of alcohol metabolism by this organism (16).…”
mentioning
confidence: 99%
“…In S. solfataricus, besides Sso2536, 12 additional open reading frames (ORFs) encoding putative ADHs have been identified and annotated (adh-1 to -13). All but adh-9 are actively expressed, as demonstrated by proteome analyses (17,18). The presence of multiple ADH ORFs indicates a metabolic relevance of alcohol metabolism by this organism (16).…”
mentioning
confidence: 99%
“…Comparative lipidomics analysis has been applied to study the ethanologenic yeast response to different inhibitors, such as furfural, acetic acid, and phenol (69). The results of comparative proteome analysis (8,23) and small-molecule metabolite profiling of ethanologenic yeast during industrial fermentation (13) have been previously reported, enhancing the molecular understanding of physiological adaptation of industrial strains for optimizing the performance of industrial bioethanol fermentation. However, the specifics of global protein expression in response to the presence of biomass conversion inhibitors have not yet been quantitatively measured for ethanologenic yeast.…”
mentioning
confidence: 99%
“…The presumably zinc-containing L-threonine dehydrogenase from T. kodakaraensis was highly stable, and this dehydrogenase had a half-life at 85°C of more than 2 h (5). In the family of zinc-containing ADHs, those from the hyperthermophilic archaea T. kodakaraensis, P. horikoshii, S. solfataricus, and A. pernix contain both catalytic and structural zincs and have been extensively studied in terms of structure, catalysis, function, or regulation (2,16,19,(25)(26)(27)(28)52). However, no ADHs containing only catalytic zinc have been characterized for Thermococcus species yet.…”
mentioning
confidence: 99%